Adaptive Project Management Model For The International Development And Aid Projects - Saleh, Firas Izzat Mahmoud Mahmoud (2022)
With the increase of natural disasters and man-made crises and the rising levels of poverty and inequality globally, the International Non-Governmental Organisations (INGOs) sector has rapidly grown in response to humanitarian emergencies and the provision of aid to support social and economic development worldwide. INGOs realise their human goals through crossing the borders to diverse, vulnerable communities and contexts to implement International Development and Aid Projects (IDAPs). However, this diversity and the specific nature of these projects have created various complexities that diminished their success and sustainability. Therefore, this industry needs an adaptive Project Management Model (PM-Model) to suit the broader organisational aspects of IDAPs and industry-specificities to increase the success levels of projects. This study aims to provide an adaptive PM-Model for IDAPs based on the standard PMBOK® Guide integrating TQM as a relevant organisational approach and Core Humanitarian Standard (CHS) as a relevant industry-specificities. Therefore, to meet the broader and longer-term organisational and social aspects. To that end, a three-round Delphi research process has been conducted to engage a group of experts to develop the required adaptations on the PMBOK® Guide and then validate the emerged PM-Model by another group of practitioners through Focus Group Discussion (FGD) validation workshop setting.